The Influence of Work Ability and Work Ethic on Employee Performance at the Regional Disaster Management Agency of Sibolga City - Alifia Chairunnisa Situmeang; Nelly Azwarni Sinaga; Muhammad Iqbal Batubara (Journal of Economics, Management and Accounting (JEMA), 2025)
This study aims to analyze the influence of work ability and work ethic on employee performance at Badan Penanggulangan Bencana Daerah Kota Sibolga. The research employed a quantitative approach with data collected through questionnaires distributed to 53 respondents. Data analysis included validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²) using SPSS. The results indicate that partially, work ability and work ethic have a positive and significant effect on employee performance. Simultaneously, both variables significantly affect performance with an F-value of 16.29 > 3.18. The coefficient of determination (R²) of 0.399 shows that work ability and work ethic contribute 39.9% to employee performance, while the remaining percentage is influenced by other factors outside this study. Work ability is identified as the most dominant variable affecting employee performance.